2023
DOI: 10.1136/ard-2023-224803
|View full text |Cite
|
Sign up to set email alerts
|

Bimekizumab treatment in patients with active axial spondyloarthritis: 52-week efficacy and safety from the randomised parallel phase 3 BE MOBILE 1 and BE MOBILE 2 studies

Xenofon Baraliakos,
Atul Deodhar,
Désirée van der Heijde
et al.

Abstract: ObjectivesBimekizumab (BKZ), a monoclonal IgG1 antibody that selectively inhibits interleukin (IL)-17F in addition to IL-17A, has demonstrated superior efficacy versus placebo in patients with non-radiographic (nr-) and radiographic (r-) axial spondyloarthritis (axSpA) at Week 16. Here, the objective is to report the efficacy and safety of BKZ at Week 52.MethodsBE MOBILE 1 (nr-axSpA;NCT03928704) and BE MOBILE 2 (r-axSpA;NCT03928743) comprised a 16-week, double-blind, placebo-controlled period, then a 36-week m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Together with previously published efficacy and safety data, 13 results from the BE MOBILE 1 and BE MOBILE 2 studies support the long-term efficacy of bimekizumab in improving clinical outcomes and alleviating the impact of axSpA on patients’ lives. Results from open-label extension studies and real-world evidence reporting will be important to confirm these findings.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Together with previously published efficacy and safety data, 13 results from the BE MOBILE 1 and BE MOBILE 2 studies support the long-term efficacy of bimekizumab in improving clinical outcomes and alleviating the impact of axSpA on patients’ lives. Results from open-label extension studies and real-world evidence reporting will be important to confirm these findings.…”
Section: Discussionsupporting
confidence: 67%
“… 11 12 Bimekizumab has demonstrated sustained efficacy and was well tolerated up to 52 weeks in patients with nr-axSpA and r-axSpA in the parallel phase 3 studies BE MOBILE 1 (NCT03928704) and BE MOBILE 2 (NCT03928743), and up to 5 years in patients with r-axSpA in the phase 2b trial BE AGILE (NCT02963506) and its open-label extension (NCT03355573). 13 14 …”
Section: Introductionmentioning
confidence: 99%
“…Bimekizumab, which recently completed the phase III program in axSpA, selectively inhibits both IL-17A and IL-17F cytokines. Recently, a placebo-controlled trial demonstrated the clinical efficacy of bimekizumab in both r-axSpA and nr-axSpA [54]. Nevertheless, the study did not yet focus on the impact of bimekizumab on structural damage in axSpA; therefore, this remains an ongoing area of research.…”
Section: Disease-modifying Anti-rheumatic Drugsmentioning
confidence: 99%
“…Patients in the BE MOBILE 2 trial were adults diagnosed with active axSpA, defined as BAS-DAI ≥ 4 and spinal pain (BASDAI Q2) ≥ 4, who had r-axSpA fulfilling modified New York (mNY) criteria [14]. All patients in BE MOBILE 2 also fulfilled ASAS criteria [13].…”
Section: Populations Of Interestmentioning
confidence: 99%
“…Bimekizumab (BKZ), a humanized monoclonal IgG1 antibody that selectively inhibits IL-17F in addition to IL-17A, has recently received European Medicines Agency approval as a novel treatment of axSpA, providing a new therapeutic option to the approved IL-17A inhibitors secukinumab (SEC) and ixekizumab (IXE) [7][8][9]. BKZ treatment has demonstrated sustained long-term efficacy, safety, and tolerability up to 5 years in the phase 2b BE AGILE trial and its openlabel extension in patients with active r-axSpA [10][11][12], and up to 52 weeks in patients across the axSpA spectrum in the parallel phase 3 studies BE MOBILE 1 (nr-axSpA) and BE MOBILE 2 (r-axSpA) [13,14].…”
Section: Introductionmentioning
confidence: 99%